Pengaruh Lingkungan Kerja Fisik dan Budaya Kerja terhadap Efektivitas Kerja pada Divisi Administrasi PT Mitsuba Indonesia Kota Tangerang - Oktaviani Dwi Prastiwi; Suryanto Sosrowidigdo; Siti Nurjanah (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2026)
This research aims to examine the relationship between physical work environment conditions and work culture with the work effectiveness of employees of the Administration Division of PT Mitsuba Indonesia. The company operates in the manufacturing of automotive components and is located in Tangerang City. The background of this research is based on field findings that although the company's physical facilities are already relatively good, the level of employee compliance with company rules is not fully consistent, so there is an allegation that there is an imbalance between the physical aspect and the aspect of work culture that can affect the overall effectiveness of work. The approach used was quantitative associative, with all 54 employees in the division involved as respondents with the application of saturated sampling techniques. Data acquisition was carried out through questionnaires and direct observation and documentation studies, then analyzed showing that both physical work environment conditions and work culture have a positive and partially significant influence on work effectiveness, with contributions of 13.3% and 5.6% respectively while simultaneously the two variables contribute 28.2%. These findings reflect that increasing work effectiveness needs to be supported through the management of physical work environment conditions and the continuous strengthening of work culture.